2002
DOI: 10.1152/physiolgenomics.00110.2002
|View full text |Cite
|
Sign up to set email alerts
|

Time course of skeletal muscle repair and gene expression following acute hind limb ischemia in mice

Abstract: DNA microarrays were used to measure the time course of gene expression during skeletal muscle damage and regeneration in mice following femoral artery ligation (FAL). We found 1,289 known sequences were differentially expressed between the FAL and control groups. Gene expression peaked on day 3, and the functional cluster "inflammation" contained the greatest number of genes. Muscle function was depressed for 3 days postligation, but returned to normal by day 7. Decreased muscle function was accompanied by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
89
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 25 publications
16
89
1
Order By: Relevance
“…Although we did not quantitatively measure more factors, previous studies have confirmed the remarkable release of many cytokines in acute ischemic tissues. [15][16][17][18] Second, our in vitro study found that total tissue protein extracted from acute ischemic limbs increased the survival, adhesion, and migration of BMCs to a much greater extent than total tissue protein extracted from chronic ischemic or normal non-ischemic limbs. Although we do not know the precise mechanism, we speculate that it is because of increased expression of some beneficial factors among the total cytokines.…”
Section: Discussionmentioning
confidence: 73%
“…Although we did not quantitatively measure more factors, previous studies have confirmed the remarkable release of many cytokines in acute ischemic tissues. [15][16][17][18] Second, our in vitro study found that total tissue protein extracted from acute ischemic limbs increased the survival, adhesion, and migration of BMCs to a much greater extent than total tissue protein extracted from chronic ischemic or normal non-ischemic limbs. Although we do not know the precise mechanism, we speculate that it is because of increased expression of some beneficial factors among the total cytokines.…”
Section: Discussionmentioning
confidence: 73%
“…SOCS-3 mRNA expression is increased during cardiotoxin-induced muscle regeneration in the tibalis anterior muscle, and SOCS-3 protein expression is elevated during early stages of plantaris muscle hypertrophy induced by the synergist ablation model. 2 In support of these findings Paoni et al (51) found that during ischemia-induced muscle regeneration there was a significant up-regulation of SOCS-3 mRNA expression as measured by microarray analysis. This suggests that in the whole animal the up-regulation of SOCS-3 expression in skeletal muscle may contribute to the myogenesis process during the recovery from muscle damage or increased loading of the muscle, and the up-regulation of SOCS-3 expression may be induced by IGF-I.…”
Section: Fig 10mentioning
confidence: 78%
“…To determine whether HIF1α regulates adult skeletal myogenesis, we employed the femoral artery ligation (FAL) model of PAD (Borselli et al, 2010;Paoni et al, 2002). In this model, hindlimb ischemia injures skeletal muscle.…”
Section: Pax7mentioning
confidence: 99%
“…In murine models of PAD (Paoni et al, 2002;Borselli et al, 2010), hindlimb ischemia leads to adult muscle injury and subjects these damaged fibers, as well as adjacent PAX7 + progenitors, to O 2 deprivation. Upon revascularization and restored perfusion, muscle fiber regeneration ensues.…”
Section: Introductionmentioning
confidence: 99%